2014
DOI: 10.1038/srep05070
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Functional Novelty of Pancreatic Ribonuclease: a Study of Musteloidea (order Carnivora)

Abstract: Pancreatic ribonuclease (RNASE1) is a digestive enzyme that has been one of the key models in studies of evolutionary innovation and functional diversification. It has been believed that the RNASE1 gene duplications are correlated with the plant-feeding adaptation of foregut-fermenting herbivores. Here, we characterized RNASE1 genes from Caniformia, which has a simple digestive system and lacks microbial digestion typical of herbivores, in an unprecedented scope based on both gene sequence and tissue expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 65 publications
1
18
0
1
Order By: Relevance
“…It was found that RNASE1 copies of different species formed respective monophyletic groups. From the phylogenetic tree, a total of nine species-specific duplication of RNASE1 were identified, including duplications in the rat, the little brown bat, the guinea pig, the naked mole rat, the African elephant (Goo and Cho 2013), the Colobinae (Zhang et al 2002), the Mustelidae (Liu et al 2014), the Bovidae and the Camelidae. This suggested strongly that duplication events occurred after the divergence from the last common ancestor of mammals (supplementary figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that RNASE1 copies of different species formed respective monophyletic groups. From the phylogenetic tree, a total of nine species-specific duplication of RNASE1 were identified, including duplications in the rat, the little brown bat, the guinea pig, the naked mole rat, the African elephant (Goo and Cho 2013), the Colobinae (Zhang et al 2002), the Mustelidae (Liu et al 2014), the Bovidae and the Camelidae. This suggested strongly that duplication events occurred after the divergence from the last common ancestor of mammals (supplementary figs.…”
Section: Resultsmentioning
confidence: 99%
“…RNASE1 gene duplication has been found in many mammals with multi-compartmentalized stomachs, such as ruminants (e.g., cows, sheep, and camels) (Kleineidam et al 1999; Breukelman et al 2001), and species with ruminant-like or cecal digestions (e.g., leaf-eating colobines and elephants) (Zhang et al 2002; Yu et al 2010; Goo and Cho 2013; Zhou et al 2014). Gene duplication of RNASE1 is believed to be correlated with the plant-feeding adaptation of foregut-fermenting herbivores (Liu et al 2014), and ruminant artiodactyls have considerably higher concentrations of pancreatic RNASE1 than other mammals (Zhang 2006). However, it is still not clear whether cetacean RNASE1 has experienced a special evolutionary trajectory during the dietary switch from ancestral herbivorous to extant carnivorous.…”
Section: Introductionmentioning
confidence: 99%
“…Both these proteins play an important role in the synthesis of lactose (Landers et al, 2009), which coincides with higher synthesis of lactose in middle lactation compared with 0.5 mo. Ribonuclease pancreatic, which is another highabundant enzyme, is involved in degrading bacterial RNA and nutrient uptake in the intestinal tract and is especially important for plant-eating animals such as cows (Liu et al, 2014). The relative high concentration of ribonuclease pancreatic in this early-lactation stage may be related to the immature digestion system of calves in the early lactation.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, however, there is no conclusive evidence to support this hypothesis . Likewise, more research is needed to understand the functional significance of RNASE1 duplications in carnivores . Nevertheless, the parallel evolution of a digestive system and the convergent adaptation of digestive enzymes in ruminants and colobines illustrate the power that common selective pressures can have, especially when related to diet.…”
Section: Ribonuclease and Lysozymementioning
confidence: 99%